Discounting financial literacy: time preferences and participation in financial education programs - Stephan Meier; Charles D. Sprenger (Institute for the Study of Labor (IZA), 2008)
Many policy makers and economists argue that financial literacy is key to financial well-being. But why do many individuals remain financially illiterate despite the apparent importance of being financially informed? This paper presents results of a field study linking individual decisions to acquire personal financial information to a critical, and normally unobservable, characteristic: time preferences. We offered a short, free credit counseling and information program to more than 870 individuals. About 55 percent chose to participate. Independently, we elicited time preferences using incentivized choice experiments both for individuals who selected into the program and those who did not. Our results show that the two groups differ sharply in their measured discount factors. Individuals who choose to acquire personal financial information through the credit counseling program discount the future less than individuals who choose not to participate. Our results suggest that individual time preference may explain who will and who will not choose to become financially literate. This has implications for the validity of studies evaluating voluntary financial education programs and policy efforts focused on expanding financial education.
urn:nbn:de:101:1-2008060511
Keywords: D14; 330; Financial literacy; time preferences; selection; field experiment; Kapitalanlage; Sparen; Wissen; Informationsverhalten; Bildungsverhalten; Zeitallokation; Feldforschung; Bildungspolitik; USA